FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS KARYAWAN: STUDI TENTANG KOMPENSASI, FLEKSIBILITAS KERJA, DAN WORK-LIFE BALANCE - Kusmana, Agus; Ali, Syarif; Supriadi, Yudi Nur; Nugroho, Setyo; Ridho, Muhammad Rasyid; Ramadhan, Satria Rizky (Gapenas Publisher, 2024)
This study aims to analyze the impact of compensation, work flexibility, and work-life balance on employee loyalty within furniture companies in the Jabodetabek region. Utilizing a quantitative approach, this research involves 40 respondents who are employees of the company. The analysis methods employed include validity tests, reliability tests, R-Square analysis, and hypothesis testing, conducted using SmartPLS 4.0. The results indicate that compensation, work flexibility, and work-life balance have a significant and positive effect on employee loyalty. These findings highlight the importance of implementing human resource management strategies that focus on employee needs, such as providing fair compensation, offering work flexibility, and supporting work-life balance. This, in turn, leads to increased employee loyalty, ultimately enhancing organizational retention and performance. The study provides valuable insights for practitioners and human resource managers in designing effective policies to create a work environment that fosters employee loyalty and productivity